Bipiperidinyl Derivatives of Cannabidiol Enhance Its Antiproliferative Effects in Melanoma Cells - Peihong Lyu; Huifang Li; Junzhao Wan; Ying Chen; Zhen Zhang; Panpan Wu; Yinsheng Wan; Navindra P. Seeram; Jean Christopher Chamcheu; Chang Liu; Hang Ma (Antioxidants, 2024)
Cannabis and its major cannabinoid cannabidiol (CBD) are reported to exhibit anticancer activity against skin tumors. However, the cytotoxic effects of other minor cannabinoids and synthetic CBD derivatives in melanoma are not fully elucidated. Herein, the antiproliferative activity of a panel of phytocannabinoids was screened against murine (B16F10) and human (A375) melanoma cells. CBD was the most cytotoxic natural cannabinoid with respective IC50 of 28.6 and 51.6 μM. Further assessment of the cytotoxicity of synthetic CBD derivatives in B16F10 cells identified two bipiperidinyl group-bearing derivatives (22 and 34) with enhanced cytotoxicity (IC50 = 3.1 and 8.5 μM, respectively). Furthermore, several cell death assays including flow cytometric (for apoptosis and ferroptosis) and lactate dehydrogenase (for pyroptosis) assays were used to characterize the antiproliferative activity of CBD and its bipiperidinyl derivatives. The augmented cytotoxicity of 22 and 34 in B16F10 cells was attributed to their capacity to promote apoptosis (as evidenced by increased apoptotic population). Taken together, this study supports the notion that CBD and its derivatives are promising lead compounds for cannabinoid-based interventions for melanoma management.